2022
DOI: 10.1093/glycob/cwac060
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of glycation in the pathology of various non-communicable diseases along with novel therapeutic strategies

Abstract: Glycation refers to carbonyl group condensation of the reducing sugar with the free amino group of protein which forms Amadori products and advanced glycation end products (AGEs). These AGEs alter protein structure and function by configuring a negative charge on the positively charged arginine and lysine residues. Glycation plays a vital role in the pathogenesis of metabolic diseases, brain disorders, aging, and gut microbiome dysregulation with the aid of three mechanisms: 1) formation of highly reactive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…As tea polyphenols, the antioxidant activity of EGC and EGCG was related to their electron‐rich conjugated system and phenolic groups. As strong nucleophiles, they can inhibit the formation of Schiff bases and scavenge RCS by attacking electron‐deficient centers to form adducts 31 . Compared with EGC, the galloyl moiety in EGCG led to the enhancement of activity, and the addition of the benzenetriol structure endowed EGCG with a stronger nucleophilic capacity 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As tea polyphenols, the antioxidant activity of EGC and EGCG was related to their electron‐rich conjugated system and phenolic groups. As strong nucleophiles, they can inhibit the formation of Schiff bases and scavenge RCS by attacking electron‐deficient centers to form adducts 31 . Compared with EGC, the galloyl moiety in EGCG led to the enhancement of activity, and the addition of the benzenetriol structure endowed EGCG with a stronger nucleophilic capacity 32 .…”
Section: Resultsmentioning
confidence: 99%
“…As strong nucleophiles, they can inhibit the formation of Schiff bases and scavenge RCS by attacking electron-deficient centers to form adducts. 31 Compared with EGC, the galloyl moiety in EGCG led to the enhancement of activity, and the addition of the benzenetriol structure endowed EGCG with a stronger nucleophilic capacity. 32 Thus, EGCG can trap the precursors of Schiff bases and RCS more efficiently, resulting in greater inhibition on glycation.…”
Section: Anti-glycation Properties In Vitromentioning
confidence: 99%
“…Additionally, with AGE‐RAGE interaction, various intracellular pathways are activated, such as mitogen‐activated protein kinase (MAPK), NF‐κB, and Jak/Stat resulting in the induction of oxidative stress and eventually causing various noncommunicable diseases such as diabetes, AD, and cancers 253 . Another study from our lab concluded that plasma glycation is directly proportional to oxidative stress, expression levels of Glut‐1 transporter, and fragility of erythrocytes in diabetic patients.…”
Section: Protein Glycation: Molecular Insightsmentioning
confidence: 91%
“…As a result of the Maillard reaction, dicarbonyl synthesis is a crucial step in forming AGEs 251 in our body, which gives one of the highly reactive carbonyl species known as MG. 252 Additionally, with AGE-RAGE interaction, various intracellular pathways are activated, such as mitogen-activated protein kinase (MAPK), NF-κB, and Jak/Stat resulting in the induction of oxidative stress and eventually causing various noncommunicable diseases such as diabetes, AD, and cancers. 253 Another study from our lab concluded that plasma glycation is directly proportional to oxidative stress, expression levels of Glut-1 transporter, and fragility of erythrocytes in diabetic patients. These modifications cumulatively may promote vascular complications.…”
Section: Protein Glycation: Molecular Insightsmentioning
confidence: 97%
“…Glycation reaction, also known as non-enzymatic glycosylation, is a nucleophilic addition reaction between the carboxyl group of reducing sugar and the free amino group of protein or peptide. Lysine, arginine, and the N-terminal of protein/peptide is the main potential glycosylation site [1,2]. The extent of protein glycation in health people is limited, but in these suffer from diabetes, prolonged hyperglycemia will strongly promote the glycation of hemoglobin and serum albumin [3,4].…”
Section: Introductionmentioning
confidence: 99%